Design, synthesis and fungicidal activity evaluation of novel pyrimidinamine derivatives containing phenyl-thiazole/oxazole moiety. Issue 15 (1st August 2019) - Yan, Zhongzhong; Liu, Aiping; Ou, Yingcan; Li, Jianming; Yi, Haibo; Zhang, Ning; Liu, Minhua; Huang, Lu; Ren, Jianwei; Liu, Weidong; Hu, Aixi
Graphic abstract: Highlights: T18 gave the best fungicidal activity, superior to diflumetorim, tebuconazole, and flusilazole. T18 possessed lower cell cytotoxicity than diflumetorim. Theoretical calculation indicated that the phenyl-thiazole/oxazole moiety is crucial to bioactivity. The R configuration of the target compounds may have better activity. Abstract: Diflumetorim is a member of pyrimidinamine fungicides that possess excellent antifungal activities. Nevertheless, as reported that the activity of diflumetorim to corn rust ( Puccinia sorghi ) was not ideal (EC50  = 53.26 mg/L). Herein, a series of novel pyrimidinamine derivatives containing phenyl-thiazole/oxazole moiety were designed based on our previous study and the structural characteristics of diflumetorim, synthesized and bioassayed to discover novel fungicides with excellent antifungal activities. Among these compounds, T18 gave the optimal fungicidal activity, which respectively offers control effects with EC50 values of 0.93 mg/L against P. sorghi and 1.24 mg/L against E. graminis, significantly superior to commercial fungicides diflumetorim, tebuconazole, and flusilazole. Cell cytotoxicity results suggested that compoundT18 has lower toxicities than diflumetorim. Furthermore, DFT calculation indicated that the phenyl-thiazole/oxazole moiety plays an unarguable role in the improvement of activity, which will contribute to designing and developing more potent compounds in the future.